2014
DOI: 10.3989/redc.2014.2.1087
|View full text |Cite
|
Sign up to set email alerts
|

Factores que influyen sobre la producción científica en Contabilidad en España: la opinión de los profesores universitarios de Contabilidad (II parte)

Abstract: Cómo citar este artículo/Citation: Escobar-Pérez, B.; García-Meca, E.; Larrán-Jorge, M. (2014). Factores que influyen sobre la producción científica en Contabilidad en España: la opinión de los profesores universitarios de Contabilidad (II parte). Revista Española de Documentación Científica, 37(2):e047. doi: http://dx.doi.org/10.3989/redc.2014.2.1087Resumen: Este trabajo es la segunda parte del publicado en la REDC, 2013, nº 3, e015, siendo su objetivo analizar la opinión del profesorado universitario en Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
3
0
3
Order By: Relevance
“…Thus, this study found that receiving awards, incentives or funding for researching favors scientific production, as reported in other studies. 14 , 23 This might be explained by the great economic expenses involving the process of developing a research project, its execution, and publication, which evidence that adequate and well-oriented funding of research activities would greatly contribute to the improvement of publication indexes in professors of Peruvian universities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study found that receiving awards, incentives or funding for researching favors scientific production, as reported in other studies. 14 , 23 This might be explained by the great economic expenses involving the process of developing a research project, its execution, and publication, which evidence that adequate and well-oriented funding of research activities would greatly contribute to the improvement of publication indexes in professors of Peruvian universities.…”
Section: Discussionmentioning
confidence: 99%
“…Otros factores relacionados con la poca PC fueron: el tiempo dedicado a la docencia, la alta carga lectiva que ostentan, el esfuerzo no compensado, la falta de formación metodológica, la desmotivación por el rechazo a sus proyectos, la influencia de la tradición investigativa de la universidad, contar con una figura rectora y haber participado en una atmosfera de investigación (Cañedo, Pérez, Guzmán y Rodríguez, 2010;Escobar, García y Larrán, 2014;Flores et al, 2015;Sogi et al, 2002). En nuestro estudio se hallaron similares situaciones.…”
Section: Discussionunclassified
“…Oler et al (2016) compare data on accounting with finance, management and marketing, finding that ratios of publication per faculty member are lower, there are fewer slots available for publication, and publication in top journals is more difficult to attain relative to these business disciplines. Escobar Pérez et al (2014) find that high rejection rates in accounting discourages Spanish accounting academics from doing research. Ballas & Theoharakis (2003) point out that there is no global academic accounting community, but a heterogeneous discipline with geographical and theme segmentations, often isolated and ignorant of each other.…”
Section: State Of the Artmentioning
confidence: 99%